Postoperative Immobilization After Hip Reconstruction in Cerebral Palsy: No Difference Between Hip Spica and Abduction Pillow - Vasconcellos, Alexander L.; Tagawa, Alex S.; Rhodes, Jason T.; Silveira, Lori J.; Skinner, Austin A.; Frumberg, David B. (Frontiers in Surgery, 2022)
Purpose: This study aims to compare radiographic outcomes and complication rates of immobilization with an abduction pillow to spica casting for postoperative care after a hip reconstruction with varus derotational proximal femur osteotomy (VDRO) with or without pelvic osteotomy for children with cerebral palsy (CP). Methods: 233 children (1-18 years old) diagnosed with CP that underwent VDRO with or without pelvic osteotomy were identified, of which 188 patients were immobilized with a spica cast and 45 were immobilized with an abduction pillow, based on surgeon preference. 123 (65%) in the Spica group and 21 (47%) in the pillow group had pelvic osteotomies. Demographic data and complication rates were collected. Radiographic parameters, including anatomic medial proximal femoral angle (aMPFA), acetabular index (AI) and migration percentage (MP), were measured for each patient at the completion of surgery, six weeks post-operatively, and one year post-operatively. Results: There was not a statistically significant difference in BMI (p=0.285), gender distribution(p=0.984), or median follow-up time(p=0.314) between groups. Rates of complications were consistent among groups with no differences in instances of delayed unions(p=0.10), subluxations(p=0.55), infection(p=0.71), or non-unions(p=0.10). There was no statistically significant difference in number of patients with an ideal aMPFA, AI, or MP (p=0.44, p=0.19, p=1.00) at one year post-operatively. Conclusions: Immobilization with an abduction pillow is a safe and effective alternative to hip spica casting following hip reconstruction.